IGZO synaptic thin-film transistors with embedded AlOx charge-trapping layers. (1st June 2022) - Lee, Yeojin; Jo, Hyerin; Kim, Kooktae; Yoo, Hyobin; Baek, Hyeonjun; Lee, Dong Ryeol; Oh, Hongseok
Abstract: We report the fabrication and characterization of indium gallium zinc oxide (IGZO)-based synaptic thin-film transistors. Radio-frequency magnetron-sputtered AlO x thin films are embedded in the IGZO channel as charge-trapping layers to provide synaptic behavior. The voltage pulse introduced at the gate electrodes traps or de-traps charges in the embedded AlO x layer thus modulates the channel current, which in turn leads to the ability to mimic biological synaptic behaviors such as excitonic postsynaptic current, paired-pulse facilitation, and potentiation and depression. Simulation results suggest that the device can perform properly as a synaptic unit in an artificial neural network.